Scholarship for postgraduate studies abroad in the specialty of Postharvest Phytopathology - Kanetis, Loukas (My University, 2026)
Awarded the first place in the 82nd program for postgraduate studies by the State Scholarship Foundation of the Hellenic Republic
Keywords: Natural sciences